Ceratophyllum tanaiticum Sapjeg. (Ceratophyllaceae) in the lakes of the islands in the mouth area of the Sula River (Ukraine) - Smoliar, N.; Shevchyk, V.; SolomakhaІ.; Shevchyk, T.; Solomakha, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
During the field research at the stream outlet of the Sula river (Poltava and Cherkassy region, Ukraine) on the islands of Zhovnyno and Romaniv Horb, the complexes of flooded biotopes with the rare relict plant Сeratophyllum tanaiticum Sapjeg. were revealed. At the time of investigations, this species was abundant in the lakes outside the floodplain and played a codominant role in groups of aquatic macrophytes. A characteristic feature of the described groups is a significant role of Salvinia natans, Utricularia vulgaris and hygrophytes in them, which is an indicator of the biotopes shallowness and sufficient water warming in them. Four classes of higher aquatic plants were detected in the communities with C. tanaiticum in the studied area, which significantly complemented the existing phytocenotic data on this species. At this research stage we considered it possible to assign the received geobotanical descriptions to a single association C. tanaiticum. Collecting additional phytocoenotic data will give a possibility to make a different decision in the future. С. tanaiticum is protected in the revealed locations on the territory of the national natural park «Nyzhniosulskyi». The main condition of its preservation is to maintain sufficient water level in the little lakes outside the floodplain of the islands.